2015
DOI: 10.1007/s00421-015-3204-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors underlying the perception of effort during constant heart rate running above and below the critical heart rate

Abstract: The close association between f b and RPE throughout the run at CHR - 5 and during the last 50 % of the run at CHR + 5 indicated that muscle afferents may have provided feedback from metabolic and mechanical stimuli that contributed to the perceptual responses. In addition, only RPE consistently indicated exhaustion and the current findings supported its use to monitor exercise performed at a constant HR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(44 citation statements)
references
References 48 publications
3
41
0
Order By: Relevance
“…Previous work has defined a sustainable exercise intensity as one that can be maintained for at least 30–60 minutes within the heavy exercise-intensity domain (12,25,30,49). In this study, CHR seemed to represent a sustainable intensity (T Lim = 45.48 ± 20.24 minutes), whereas PCHR did not (T Lim = 20.99 ± 17.27 minutes).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has defined a sustainable exercise intensity as one that can be maintained for at least 30–60 minutes within the heavy exercise-intensity domain (12,25,30,49). In this study, CHR seemed to represent a sustainable intensity (T Lim = 45.48 ± 20.24 minutes), whereas PCHR did not (T Lim = 20.99 ± 17.27 minutes).…”
Section: Discussionmentioning
confidence: 99%
“…For the general population, this relative intensity should reflect a significant portion of exercise within the heavy exercise-intensity domain (47). However, it is not clear where these exercise prescription recommendations place an individual relative to the exercise-intensity domains because the responses to exercise anchored by physiological parameters result in divergent responses from the power output associated with that V Ȯ2 , HR, or RPE (12,41). These differences in responses are a result of altering the external load to elicit the desired physiological intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Neuromuscular fatigue seems to be the dominant mechanism influencing perceived fatigue during the initial portion of the run. Later, the feedback from the fatiguing cardiorespiratory system might also increase the perception of effort (Bergstrom et al, 2015). Finally, as demonstrated by an increase in cardiac cost at high fatigue perception, we can argue that additional motor units are needed to produce the same overall muscle efficiency, which results in higher physiological/metabolic costs (Kounalakis et al, 2008;Marcora et al, 2008).…”
Section: Onset Of Fatiguementioning
confidence: 99%
“…All participants demonstrated very good-toexcellent physiological measures (e.g., VO 2 max , % VO 2 max at GET) during the ramped incremental trials (de Pauw et al 2013). Therefore, having a collection of participants with a narrower distribution of physiological capabilities compared to other studies (Cochrane et al 2015a;Bergstrom et al 2015) could explain the low CoV values and confidence intervals observed in this study.…”
Section: Discussionmentioning
confidence: 67%